Weight gain regardless of pre-pregnancy BMI and influence of fetal gender in response to labor induction in postdate pregnancy. (July 2013) - Torricelli, Michela; Voltolini, Chiara; Conti, Nathalie; Bocchi, Caterina; Severi, Filiberto M.; Petraglia, Felice
Abstract Objective: To evaluate whether maternal weight and body mass index (BMI) and their increase throughout pregnancy are associated with the response to labor induction in postdate pregnancies. Methods: A total of 376 nulliparous women carrying singleton postdate pregnancies with unfavorable cervix were enrolled. We considered as primary outcome vaginal delivery within 24 h after induction, and outcomes were divided into responders (n = 258) and non-responders (n = 107) to the induction of labor to perform the statistical analyses. Results: In the total population of study, women who successfully delivered within 24 h differed significantly from the remaining patients in terms of maternal weight gain (p = 0.009) and BMI increase (p = 0.02) during pregnancy. In addition, males were significantly more (p = 0.005) than females among newborns of women not responding to induction of labor. In the multivariate analysis, maternal weight gain and fetal sex significantly influenced the induction response. The occurrence of a failed induction of labor was more likely in patients presenting a greater maternal weight gain (cut-off 12 kg) and male fetus. Conclusion: Weight gain over 12 kg regardless of pre-pregnancy weight and male fetal gender are two novel potential risk factors for the prediction of failure to induction of labor in postdate pregnancy.